ANALYSIS OF BANKRUPTCY PREDICTION WITH COMPARISON OF SPRINGATE AND ZMIJEWSKI MODELS ON STATE-OWNED COMPANIES IN THE INFRASTRUCTURE SECTOR LISTED ON THE IDX - Dea Selvani; Afrah Junita; Tuti Meutia (RADJA PUBLIKA, 2022)
This study aims to determine the prediction of potential bankruptcy in State-Owned Enterprise companies in theInfrastructure sector listed on the Indonesia Stock Exchange using the Springate and Zmijewski models. The data used in this study are the company's financial statements published on the Indonesia Stock Exchange. Popolasi in this study is all 9 companies of State-Owned Enterprises in the Infrastructure sector listed on the Indonesia Stock Exchange. Sampling technique using purposive sampling, so that 7 companies can be used as research samples. The data analysis method uses bankruptcy prediction models including Springate and Zmijewski and uses different tests on both prediction models with normality test and Kruskal-Wallis H test. The results showed that the springate prediction model predicts more companies that have the potential to go bankrupt while the zmijewski model does not, the springate model has an accuracy rate of 67% in predicting bankruptcy, while the zmijewski model is only 29%, so in this study the springate model is the most appropriate model to predict company bankruptcy..